KUALITAS CHICKEN NUGGET YANG DIFORTIFIKASI DENGAN TEPUNG KACANG KEDELAI UNTUK PENINGKATAN SERAT PANGAN (DIETARY FIBER) - Mawati, Astria; Sondakh, E.H.B.; Kalele, J.A.D.; Hadju, R. (ZOOTEC, 2017)
THE QUALITY OF CHICKEN NUGGET FORTIFICATED BY SOYBEAN FLOUR ON INCREASING DIETARY FIBER. This research aimed to determine the effect of soy bean flour as fortification ingredient to increase dietary fiber products to chicken nuggets. The meat used for nuggets chicken was taken chest. Soybeans are used as a fortification ingredient for the product of chicken nuggets. This experiment using a completely randomized design with five treatments consisting of a treatment R0 level 0% of soybean of the meat composition of 400 g (0 g of soybean and 400 g of meat), R1 level of 5% of soybean of the meat composition (20 g soybean and 380 g of meat) R2 level of 10% of soy bean of the meat composition (40 g of soybean and 360 g of meat), R3 15% of soy bean of the meat composition (60 g of soybean and 340 g of meat), R4 level 20% soybean of the meat composition (80 g of soybean and 320 g of meat). Each treatment was conducted three replications. If there was a difference of average in the analysis of variance then to DMRT test. The results showed that fortification with soy beans in chicken meat had a significant on the water holding capacity and fiber dietary, while the pH of the meat is not significant. The conclusion of this study that 80 grams of soy bean flour fortified in 320 grams meat can be used for the product chicken nuggets because it can increase the content of dietary fiber.Keywords: chicken nugget, soybean flour, dietary fiber